Transformation of Students' Career Orientation in the Era of Artificial Intelligence: A Systematic Literature Review - Yupelmi, Mimi; Ganefri; Giatman, Muhammad; Krismadinata; Syah, Nurhasan (The Indonesian Journal of Computer Science, 2024)
This research revolves around the challenges faced by students in aligning their career orientation with demands and changes, as many traditional jobs are threatened by AI technology. The aim of this study is to identify trends in the transformation of students' career orientation in the era of Artificial Intelligence (AI), map the career challenges for students in the AI era, analyze the skills and competencies required, and assess the role of educational institutions in supporting this career transformation. The research method applied in this study is a systematic literature review. The initial stages involve collecting literature sources from scholarly databases and proceeding with a screening process to select literature relevant to the research focus. Finally, in-depth analysis of selected literature is conducted to identify patterns, trends, and key points related to the research topic. The results of the study describe that the development of AI technology has a significant impact on students' career orientation in higher education. Furthermore, students also face career challenges such as competition with technology, uncertainty about future employment, and skills gaps. To address these challenges, students need to develop technical AI skills, ethical AI understanding, problem-solving abilities, and continuous learning skills to succeed in the AI job market. On the other hand, higher education institutions should play a proactive role in addressing these challenges by developing relevant curricula, organizing training sessions, collaborating with industries, and enhancing AI learning facilities. Further research is suggested to focus on the implementation of these strategies in the specific context of higher education institutions and evaluate their impact on student career preparedness in the evolving AI era.